Costs and effectiveness of hearing conservation programs at 14 US metal manufacturing facilities. (26th January 2018) - Sayler, Stephanie K.; Rabinowitz, Peter M.; Cantley, Linda F.; Galusha, Deron; Neitzel, Richard L.
Abstract: Objective: This study characterised overall and specific costs associated with hearing conservation programmes (HCPs) at US metal manufacturing sites, and examined the association between these costs and several noise-induced hearing loss (NIHL) outcomes. Design: We interviewed personnel and reviewed records at participating facilities. We also measured noise for comparison to the ten-year average of measurements made by each facility. NIHL outcomes assessed included rates of standard threshold shifts (STS) and high-frequency hearing loss, as well as prevalence of hearing impairment, for each participating facility. We used linear regression to identify per-person HCP costs that best predicted the NIHL outcomes. Study sample: We evaluated 14 US metal manufacturing facilities operated by a single company. Results: Annual HCP costs ranged from roughly 67, 000 to 397, 000 (average 308 ± 80 per worker). Our full-shift noise measurements (mean 83.1 dBA) showed good agreement with the facilities' measurements (mean 82.6 dBA). Hearing impairment prevalence was about 15% overall. Higher expenditures for training and hearing protector fit-testing were significantly associated with reduced STS prevalence. Higher training expenditures were also related to lower hearing impairment prevalence and high-frequency hearing loss rates. Conclusions: HCP costs were substantial and variable. Increased workplace spending on training and fit-testing may help minimise NIHL.